1993
DOI: 10.1176/appi.psychotherapy.1993.47.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Health Care Costs of Multiple Personality Disorder

Abstract: The lifetime psychiatric health care costs of 15 women with multiple personality disorder (MPD) who were admitted to the senior author's inpatient service over a four-year period were tabulated. A calculation of the projected costs of treatment based on costs incurred since diagnosis was made, and this was compared to prediagnosis baseline costs projected forwards for ten years. The result of the calculation was a saving of $84,899.44 per patient over ten years due to the diagnosis and psychotherapeutic treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 0 publications
2
26
0
2
Order By: Relevance
“…(Canadian) in the three years after treatment for DID (Ross and Dua, 1993). This and other studies document considerable cost savings even for those who had been chronically ill before being appropriately treated for DID (Lloyd, 2011).…”
Section: Treatment Of Didsupporting
confidence: 53%
“…(Canadian) in the three years after treatment for DID (Ross and Dua, 1993). This and other studies document considerable cost savings even for those who had been chronically ill before being appropriately treated for DID (Lloyd, 2011).…”
Section: Treatment Of Didsupporting
confidence: 53%
“…These patients’ severe and chronic trauma histories are well documented, as are the many years they spend in the mental health system receiving inpatient and outpatient services (Boon & Draijer, 1993; Fraser & Raine, 1992; Hornstein & Putnam, 1992; Lloyd, 2011; Putnam, Guroff, Silberman, Barban, & Post, 1986; Ross & Dua, 1993; Ross, Joshi, & Currie, 1990). Mansfield and colleagues (2010) reported that DD patients who were spouses of active-duty U.S. military personnel utilized mental health services at a higher rate than individuals diagnosed with any of the other 16 psychiatric disorders they studied.…”
Section: Highlightsmentioning
confidence: 99%
“…Each individual suicide attempt among general psychiatric patients costs an estimated 2000–68,000 USD when direct costs such as ambulatory care, medical tests, surgeries, and psychiatric treatment are considered (reviewed in Yang & Lester, 2007). Some preliminary studies have calculated that swift and accurate diagnosis of DDs, followed by appropriate trauma- and dissociation-focused treatment, would substantially decrease the cost of DD patients’ treatments, even in cases where patients are severely impaired (Fraser & Raine, 1992; Lloyd, 2011; Ross & Dua, 1993). …”
Section: Highlightsmentioning
confidence: 99%
“…These studies' systematic data show that DID treatment consistent with the expert guidelines is associated with decreased dissociation, depression, anxiety, posttraumatic stress, general psychiatric distress, and self-destructiveness, among others (Brand, Classon, McNary, & Zaveri, 2009). In addition, cost-efficacy studies of DID treatment have shown a robust decrease in costs over years of followup, once phasic DID treatment was initiated, even in the most chronically ill DID patients (Fraser & Raine, 1992;Lloyd, 2011;Loewenstein, 1994;Ross & Dua, 1993).…”
Section: Expert Treatment Guidelines and Evidence About Did Treatmentmentioning
confidence: 99%